Seleção de sistemas de geração de energia elétrica a partir de resíduos sólidos urbanos: uma abordagem com a lógica difusa - Barin, Alexandre (2012)
Sustainability is becoming a major driving force in energy policy, leading to the development of different strategies and projects. Many of these strategies are related to the application of novel methodologies for selecting Renewable Energy Systems (RES) and energy storage systems. Electrical generation with biogas from municipal solid waste (MSW) is one of the main alternatives to concern all the conceptions of sustainability - social, economic and environmental constrains. The complexity of sustainability and energy planning makes the multicriteria analysis a valuable tool for the decision making process. The use of an effective methodology for RES selection a decision making process is essential to guarantee the adequate energy management of the biogas and the MSW landfill. This methodology must be able to balance positive and negative aspects, achieving an overall solution that best satisfies the management needs. It is essential to deal with several parameters and concern the decision maker (DM) interaction over the decision making process. By applying the DM preferences into the development of the methodology, it is possible to corroborate the methodology outcome. The presented thesis will therefore develop a novel methodology for selection of RES fuelled by biogas from MSW landfills. This methodology taking as basis fuzzy multi-rules and multi-sets to provide an accurate analysis of conflicting aspects - operational, economic, environmental, social, etc. These aspects are taken into account for each study case according to different perspectives adopted by the DMs. The novel arrangements developed in this work are the creation of a previous classification of the priority criteria, the application of meta-rules and how to structure the fuzzy rules construction. The proposed arrangements have the purpose of easing the understanding of the methodology, as well as improving the DM interaction over the decision making process achieving in this way a better solution. This work presents the application of the novel decision making process to select the most appropriate energy source fuelled by biogas from MSW, considering the Caturrita II landfill located at Santa Maria City, Brazil. In conclusion, it is important to emphasize that the novel software may be used in any energy system selection, for supplying or storage, according to the analysis of several criteria and perspectives for each regional circumstances, as well as particular management needs..